Examinations on plants soil and in grasslands of South-East Hungary: Floristical summary and the vegetation of Sap Kurgan - Herczeg, Edina; Barczi, Attila; Penksza, Károly (TÁJÖKOLÓGIAI LAPOK, 2006)
The four chosen kurgans are located in the territory of the Körös-Maros National Park (Kántor Kurgan, Bőre Kurgan, Sáp Kurgan, Bökény Kurgan). Silty grasslands of Hungary represent the westernmost occurences of East-European silty grass steppes. Generally they are the typical associations of areas with high fertility chernozem soils. At the same time, soil researches showed that the first sampling area (Kántor Kurgan) rises from a chernozem surrounding, the second one (Bökény Kurgan) from an area with meadow soil (Vertisol), and the third one (Bőre Kurgan) from a solonetz sodic area. Kurgans proved to be the most appropriate sampling areas, on the slopes of which two silt steppe associations change with a sharp boundary.